Lubang Buaya, Kuburan Para Pahlawan: Abjeksi dalam Historiografi Peristiwa 1 Oktober 1965 - Muhammad Damm (Antropologi Indonesia, 2017)
Not only explanations about 30th September Movement (G30S) on 1st October 1965 debatable, the following mass murder during late 1965 to 1966 is still far from any clearance either. How that mass murder possible? We may say, following Roosa’s argument, that that mass murder possible because of preceding pretext, that is G30S/PKI. We may also say, following Drakeley’s argument, that that mass murder possible because of current socio-political atmosphere at that time was conducive for its emergence. Nevertheless, both arguments are sufficient to explain how 1965–1966 mass murder possible if only complemented by explanation about “mental mechanism” that worked behind it. That mental mechanism, namely abjection of PKI (Communist), can be revealed through structural inquiry to The Sacred Pancasila Monument complex as a representation and reconstruction of 1st October 1965 historical event. Not only made 1965–1966 mass murder possible, abjection mechanism also legitimized New Order’s historiography about 1st October 1965. Using structural anthropology as paradigm and museum ethnography as research method, this article attempts to explain how the abjection transpired.Keywords: The Sacred Pancasila Monument, Pancasila, PKI, communist, latent danger, abjection.